2005
DOI: 10.1128/mcb.25.3.958-968.2005
|View full text |Cite
|
Sign up to set email alerts
|

Common Effects of Acidic Activators on Large-Scale Chromatin Structure and Transcription

Abstract: Large-scale chromatin decondensation has been observed after the targeting of certain acidic activators to heterochromatic chromatin domains. Acidic activators are often modular, with two or more separable transcriptional activation domains. Whether these smaller regions are sufficient for all functions of the activators has not been demonstrated. We adapted an inducible heterodimerization system to allow systematic dissection of the function of acidic activators, individual subdomains within these activators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 58 publications
4
68
0
Order By: Relevance
“…It was previously reported that targeting of either VP16 or p65 caused dramatic decondensation of non-centromeric reporter arrays (Carpenter et al, 2005). We also observed some decondensation of the HAC when targeted by p65 or VP16 (Fig.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…It was previously reported that targeting of either VP16 or p65 caused dramatic decondensation of non-centromeric reporter arrays (Carpenter et al, 2005). We also observed some decondensation of the HAC when targeted by p65 or VP16 (Fig.…”
Section: Resultssupporting
confidence: 77%
“…This domain promotes the opening of the local chromatin structure and results in a substantial increase in local RNA polymerase activity (Carpenter et al, 2005). TetR-EYFPp65 is an analogous construct that contains a minimal C-terminal trans-activation domain derived from the NF-kB subunit p65.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excellent work has been done in this field in recent years [46][47][48] . Some researchers write custom software or macros for non-high-throughput image analysis programs, but their general applicability is limited 8,13,24,40,42,[49][50][51][52][53][54][55][56][57] . A more user-friendly solution is proprietary commercial software, typically bundled with an expensive image acquisition instrument and targeted to the pharmaceutical drug screening market 58 (for screening multiwell plates) or to clinical pathology laboratories 59 (for histological slides).…”
Section: Image Analysismentioning
confidence: 99%